Makna Lughah dan Syaraʿ pada Istilah-istilah di dalam Fath al-Muʿin: Analisis Semantik Toshihiko Izutsu - Lutfi, Mukhammad; Hidayatullah, Moch. Syarif; Buana, Cahya (Kalimatuna: Journal of Arabic Research, 2023)
The most important aspect in understanding fiqh is the study of Arabic language (linguistics). Linguistics includes principles relating to the way words convey their meaning, clarity, ambiguity and interpretation. The existence of terms that have lughah and syaraʻ meaning in Fath al-Muʻin attracts researcher to examine them further through semantic studies. This research focuses its discussion on terms that are defined with the lughah and syaraʻ meaning in Fath al-Muʻin, Toshihiko Izutsu's semantic analysis is used to identify the basic meaning, relational meaning and weltanschauung that apply therein. The results show that the lughah meaning is in line with what Izutsu calls basic meaning, and the syaraʻ meaning is in line with what is called relational meaning. Of course, syaraʻ (fiqh) is a relational context, because syaraʻ is smaller than the relational meaning which is more flexible depending on the context being discussed. The weltanschauung that operates is the weltanschauung fiqh, which means that the terms with the definitions of lughah and syaraʻ must be understood in the context of the fiqh worldview.